HUBUNGAN KOMPETENSI DAN DISIPLIN KERJA DENGAN KINERJA PEGAWAI INSPEKTORAT PROVINSI JAWA TENGAH - Maudyta Maudyta; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
This research aims to find out the correlation between competence and work discipline with the performance of Inspectorate employee of Central Java Province. This research is an associative study using quantitative method. Respondents in this research is 48 employee of Inspectorate Central Java Province who performed the main task of supervision. Based on the result of the study, the Kendall Tau correlation coefficient of competence with employee performance is 0.468 with Z value 5,001 > Z table 1.96, the Kendall Tau correlation coefficient of work discipline and employee performance is 0.417 with Z value 4,373 > Z table 1.96, Kendall concordance correlation 0,851 sig (0,000) < α (0,005) indicate that there is a correlation between competence and work discipline with the performance of inspectorate employee of Central Java province. The determinant coefficient value of competence and work discipline variable simultaneously gives influence to the employee performance variable amounted to 72.4%. The conclusion of the study is there is a correlation between competence and work discipline with the employee performance of Inspectorate Central Java province, so the H1 is accepted and H0 is rejected. The obstacles found in the study are less ability of the employee in applying the benefit of training, the training activity was not conducted regularly, and it was found that the employee presence was not timely. The suggestions can be given by researcher are off-the-job training method should be conducted regularly and Inspector should take corrective disciplinary action.